2021
DOI: 10.1038/s41598-021-99170-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping thalamocortical functional connectivity with large-scale brain networks in patients with first-episode psychosis

Abstract: Abnormal thalamocortical networks involving specific thalamic nuclei have been implicated in schizophrenia pathophysiology. While comparable topography of anatomical and functional connectivity abnormalities has been reported in patients across illness stages, previous functional studies have been confined to anatomical pathways of thalamocortical networks. To address this issue, we incorporated large-scale brain network dynamics into examining thalamocortical functional connectivity. Forty patients with first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…In another study involving first-episode psychotic patients, heightened functional connectivity to nodes of the default mode network and central executive network was observed in the dorsal pulvinar. This finding aligns with our multimodal model, wherein increased expression of D2 receptors corresponds to this region (Kwak et al 2021).…”
Section: Neurochemical Correlates Of Pulvinar-cortical Topographical ...supporting
confidence: 91%
“…In another study involving first-episode psychotic patients, heightened functional connectivity to nodes of the default mode network and central executive network was observed in the dorsal pulvinar. This finding aligns with our multimodal model, wherein increased expression of D2 receptors corresponds to this region (Kwak et al 2021).…”
Section: Neurochemical Correlates Of Pulvinar-cortical Topographical ...supporting
confidence: 91%
“…While functional dysconnectivity between the cortex and the entire thalamus as a region of interest (ROI) has been relatively well established 32 – 34 , studies have used segmented thalamic ROIs based on the functional connectivity (FC) of each thalamic voxel to anatomically parsed cortical lobes. These studies have revealed consistent dysconnectivity with posterior cerebellar clusters and the cortical areas that are often referred to as the nodes of higher-order cognitive networks in not only chronic schizophrenia patients 35 , 36 but also first-episode psychosis (FEP) and clinical high-risk (CHR) patients 37 – 39 .…”
Section: Introductionmentioning
confidence: 90%
“…A total of 39 patients with FEP, 78 subjects at CHR for psychosis, and 110 healthy controls (HCs) participated in this study. Resting-state functional magnetic resonance imaging (rs-fMRI) data from 39 FEP patients and 40 HCs were used in our previous study [ 19 , 20 ], and data from 110 HCs were used in other studies [ 21 , 22 ]. FEP patients and individuals at CHR for psychosis were recruited from the Seoul Youth Clinic (www.…”
Section: Methodsmentioning
confidence: 99%